Rule your day : 6 keys to maximizing your success and accelerating your dreams - Osteen, Joel (FaithWords, 2022)
"Some people live in a constant state of worry, upset, and negativity because they let everything in. They listen to the news all day, go to lunch with judgmental people, or get cut off in traffic, leaving the rest of their day pretty sour. They're not ruling their day. No one can keep all bad things from happening, but you can stop them from getting down in your spirit. The less time you spend in bad situations or with small-minded people, the better off you're going to be. Don't sit inactive with people who don't believe in you, people who don't come into agreement with your dreams. You control what you allow into your day, your mind. God has given you the authority to rule over your attitude and your response. Let God control what you can't. If you'll do your part, then He will do His-making things happen that you couldn't even imagine. With Rule the Day, you'll be able to go out each day expecting the best, knowing everything may not be perfect. There may be delays, interruptions, difficult people, but you'll learn to not let these things ruin your day. Know that God is directing your steps and has given you the power to remain calm in times of adversity. Every day can be a good day, if you rule your atmosphere"--